ECO-MODERATISM: THE VIEW AND ATTITUDE OF NAHDLATUL ULAMA IN RESPONSE TO ENVIRONMENTAL CRISIS - Rahwan, Rahwan; Rohman, Saifir; Hosaini, Hosaini (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This research seeks to reveal the views and attitudes of Nahdlatul Ulama in responding to the environmental crisis. With the qualitative method of literature and descriptive analysis the research concluded two things. First, Nahdlatul Ulama's views in responding to the environmental crisis reflect an eco-moderate approach, namely based on moderate values as a basis for thinking and acting. Nahdlatul Ulama's view of eco-moderatism is reflected in several ways. Among other things, balancing between the permissibility of utilizing nature and the environment with the obligation to preserve it. In formulating religious views regarding the environmental crisis, Nahdlatul Ulama has proportionally combined the use of revelation and reason. In addition, Nahdlatul Ulama also provides views that protect collective and individual benefits. Second, in line with this eco-moderate view, Nahdlatul Ulama has responded to the environmental crisis by taking concrete actions and movements, including forming the Nahdlatul Ulama Institute for Disaster Management and Climate Change (LPBI-NU). Through this institution, NU has carried out many environmental care programs such as establishing a Compost House, the Nusantara NU Waste Bank (BSN-NU), and Paying for Plastics.